BAHAYA GADGET DAN BULLIYING SERTA EDUKASI PUBERITAS PADA ANK USIA SEKOLAH DASAR DALAM MENGHADAPI MASA REMAJA DI SDIT AL USWAH 1 BANYUWANGI - Masroni, Masroni; Izzah, Ukhtul; Ariyani, Dwi; Damayanti, Fransiska Erna (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Nowdays technological developments are very rapid, a gadget can be defined as a tool that can be easily connected to the internet. If you use gadgets wisely, you will get many benefits. However, if gadget use cannot be controlled it will have a negative impact. One of the negative impacts is dependence or addiction to gadgets. Apart from the use of gadgets, bullying also often occurs nowadays. Around three million children are addicted to gadgets, bullying behavior and abuse in the school environment. Efforts to increase children's awareness regarding the dangers of bullying and the use of gadgets as well as puberty education can be done through health promotion, programs created in schools can be more focused and cost-effective. Health education is one of the effective promotive and preventive efforts that can be carried out to increase the knowledge of students and female students which can influence changes in a person's behavior in order to prevent acts of violence, bullying, or excessive use of technological tools, in addition to achieving personal readiness in facing puberty.